Internet and social media as allies of the extension actions of the Good Practices Project during the Covid-19 Pandemic - Gonçalves dos Santos, Jéssica; Barcelos de Aquino, Maria Clara; Batista de Azevedo, Letícia; de Souza Couto Oliveira, Jhenifer; Freitas Brilhante de São José, Jackline (Guará Journal, 2022)
The  health  crisis  imposed  by  the  COVID-19  pandemic caused  changes  in  universities,  which  needed  to organize  themselves  to  ensure  the  development  of academic  activities,  such  as  extension  projects.  The present  work  aimed  to  report  the  use  of  the  internet  and  social  media  as  extension  strategies develo-ped  by  the  ‘Project  Good  Manipulation Practices  in  Food  Ser-vices:  Assessment  and  Guidance  for  the  Production  of  Safe  Foods’  during the  COVID-19  pandemic.  The  activities  reported  were carried  out  between  April  2020  and  May  2022. Remote  meetings  have  been  conducted  to  reorganize  the  proposed  activities,  such  as  preparing  instructional  materials  and  creating an Instagram profile. The extension team developed these activities. As a result, three materials about   food safety and COVID-19  were  prepared.  In  addition,  content related  to  the  pro-ject’s theme was shared on Instagram, totaling 91 publications. Materials and the social network had repercussions on the target audience and demonstrated the importance of adapting to extension  activities.  The  importance  of  using  the internet  and  social  networks  in  extension  activities  is evident,  as  they  add  value to the student’s learning process and give the target au-dience greater access to the extension project.
Keywords: COVID-19; Pandemic; Health education; Social network; Food Quality